A soft switching with reduced voltage stress ZVT-PWM full-bridge converter - Sahin, Yakup; Ting, Naim Suleyman; Acar, Fatih (AIP Publishing, 2018)
This paper introduces a novel active snubber cell for soft switching pulse width modulation DC-DC converters. In the proposed converter, the main switch is turned on under zero voltage transition and turned off under zero voltage switching (ZVS). The auxiliary switch is turned on under zero current switching (ZCS) and turned off under zero current transition. The main diode is turned on under ZVS and turned off under ZCS. All of the other semiconductors in the converter are turned on and off with soft switching. There is no extra voltage stress on the semiconductor devices. Besides, the proposed converter has simple structure and ease of control due to common ground. The detailed theoretical analysis of the proposed converter is presented and also verified with both simulation and experimental study at 100 kHz switching frequency and 600 W output power. Furthermore, the efficiency of the proposed converter is 95.7% at nominal power. Published by AIP Publishing.
Keywords: DC-DC CONVERTER; BOOST CONVERTER; DESIGN; IMPLEMENTATION; Instruments & Instrumentation; Physics